Job satisfaction of generation Z employees in the Solo Raya Region - Frendy Wibowo; Hapsari Dyah Herdiany Hapsari; Pradita Nindya Aryandha; Tuffah Fahmi Abdat; Luthfiah Mumtaz (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2026)
This study aims to analyze the effect of work-life balance and workload on job satisfaction, with organizational culture serving as an intervening variable among Generation Z employees in Solo Raya. Using a quantitative approach and Structural Equation Modeling (SEM), the study evaluates both direct and indirect relationships between variables. This study involved 200 Gen Z employees in the Greater Solo Area. The findings of this study indicate that Gen Z employees who balance work demands with their personal lives tend to develop positive perceptions of their jobs, ultimately leading to higher levels of job satisfaction. Well-managed workloads directly enhance satisfaction by fostering psychological adaptation in the form of increased tolerance and a strengthened sense of competence, which subsequently contributes to greater job satisfaction. A supportive, inclusive, and adaptive organizational culture—particularly one aligned with Gen Z's characteristics—amplifies the positive effects of work–life balance and mitigates the negative impact of workload, resulting in higher overall job satisfaction. The mediating effect of organizational culture provides insight into how individual factors do not solely shape job satisfaction among Gen Z employees but are also strongly influenced by the organizational context. These findings show that HR strategies should reflect the new generation's unique characteristics, and organizations should build an inclusive, supportive work culture that supports individual balance to improve employee satisfaction and retention.